(untitled) (Dhaka University Journal of Pharmaceutical Sciences, 2025)
Chalcones are unsaturated 1,3-diaryl ketones, which can act as precursors of many bioactive heterocyclic compounds like pyrimidines, pyrazoles, and so on. Pyrazoles are also well-known to offer hundreds of bioactive moieties. Cancer and oxidative stress are two vital concerns in the present world. In the present investigation, a chalcone named as (E)-3-(4-nitrophenyl)-1-phenyl-prop-2-en-1-one (1) was produced by the reaction of 4-nitrobenzaldehyde with acetophenone. It was then treated with hydrazine hydrate, and hydrazine hydrate with acetic acid to obtain two pyrazoles, 5-(4-nitrophenyl)-3-phenyl-4,5-dihydro-1H-pyrazole (2), and 1-(5-(4-nitrophenyl)-3-phenyl-4,5-dihydropyrazol-1-yl) ethenone (3), respectively. The structures of the compounds were deduced by using FT-IR, 1H NMR, and 13C NMR analyses. Compounds 1-3 showed noticeable cytotoxicity on HeLa cell line. Antioxidant potentials of compounds 1-3 were also prominent. Additionally, in silico drug likeness properties and drug-receptor docking with epidermal growth factor receptor (EGFR) were also performed. It provided ideas on their pharmacokinetic and drug-receptor binding features. Based on the overall study, the compounds 1-3 might be considered as lead molecule. Further comprehensive studies are required to know their detail mechanism of the observed biological activities. Dhaka Univ. J. Pharm. Sci. 24(1): 95-104, 2025 (June)